Associations among perceived taste and smell sensitivity, gastrointestinal symptoms, and restrictive eating in a community sample of adults. (August 2022) - Pucci, Gabriella; Forney, K. Jean
Abstract: Restrictive eating is associated with several poor health outcomes. Exteroceptive sensory modalities, including taste and smell, are employed while eating and disturbances in exteroceptive sensitivity may influence eating behavior. Meal-related gastrointestinal disturbances, such as early satiety and postprandial fullness, are well-documented in eating disorders and may influence eating behavior. This study examined the relationships of perceived sensitivity to taste or smell and gastrointestinal symptoms with restrictive eating, and potential interactions between gastrointestinal symptoms and perceived sensitivity to taste or smell. Adults aged 18–65 were recruited via ResearchMatch.org ( N = 420) and completed questionnaires assessing restrictive eating, perceived sensitivity to taste and smell, and gastrointestinal symptom severity. There was a weak relationship between restrictive eating and perceived sensitivity to taste ( r = −0.115, p = .022) and smell ( r = −0.101, p = .039). There was a strong relationship between gastrointestinal symptom severity and restrictive eating ( r = 0.583, p < .001). Gastrointestinal symptom severity moderated the relationship between perceived sensitivity to taste and restrictive eating, such that this relationship was strongest at lower levels of gastrointestinal symptom severity (Estimate = −0.136, p = .014). There was no observed interaction between perceived sensitivity to smell and gastrointestinal symptoms (Estimate = 0.001, p = .156). Results indicate that increased perceived sensitivity to taste, smell, and gastrointestinal symptom severity were each associated with greater restrictive eating. The relationship between perceived sensitivity to taste and restrictive eating is strongest at lower gastrointestinal symptom severity. Future research should examine whether tailoring treatments for individuals who present with elevated perceived sensitivity to taste or smell, gastrointestinal symptoms, or both is effective in reducing restrictive eating. Highlights: Perceived sensitivity to taste and smell were weakly correlated with restriction. Gastrointestinal symptoms were strongly correlated with restriction. At low gastrointestinal symptoms, taste sensitivity was correlated with restriction. At high gastrointestinal symptoms, taste sensitivity was not related to restriction. Maintenance models for restriction should incorporate conditional relationships.